Trace Element Analysis of Lithic Artifacts from the Trapps Gap Site - C. B. Rieth; Johnson, L. L. (Current Research in New York State Archaeology: A.D. 700-1300, 2011)
Traditional models of Late Prehistoric (A.D. 700–1300) interaction in the middle Hudson Valley suggest strong ties with contemporaneous groups in southern New England. Recent research, in the form of trace element analysis of lithic artifacts from the Trapps Gap site in Ulster County, New York, questions this assumption suggesting a more diverse and complex landscape in which groups interacted. This paper will discuss whether all of the samples were procured from the same deposit, how such procurement patterns may have changed over time, and what such data might reveal about regional behavior.
Keywords: anthropology